2017
DOI: 10.1038/s41598-017-17058-x
|View full text |Cite
|
Sign up to set email alerts
|

Altered human voice processing in the frontal cortex and a developmental language delay in 3- to 5-year-old children with autism spectrum disorder

Abstract: The inferior frontal and superior temporal areas in the left hemisphere are crucial for human language processing. In the present study, we investigated the magnetic mismatch field (MMF) evoked by voice stimuli in 3- to 5-year-old typically developing (TD) children and children with autism spectrum disorder (ASD) using child-customized magnetoencephalography (MEG). The children with ASD exhibited significantly decreased activation in the left superior temporal gyrus compared with the TD children for the MMF am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…Because it is difficult to obtain individual magnetic resonance images from young children, we used a child brain template using a modified version of the estimation algorithm reported in previous studies (Hayashi et al, ; Yoshimura et al, ). The algorithm determined an optimal brain structure image from 98 young children's brain images based on the individual head surface.…”
Section: Methodsmentioning
confidence: 99%
“…Because it is difficult to obtain individual magnetic resonance images from young children, we used a child brain template using a modified version of the estimation algorithm reported in previous studies (Hayashi et al, ; Yoshimura et al, ). The algorithm determined an optimal brain structure image from 98 young children's brain images based on the individual head surface.…”
Section: Methodsmentioning
confidence: 99%
“…The method of MMF analysis is based on our previous research 34 . Magnetic fields were measured using a whole-head MEG system for adults in a magnetically shielded room (Daido Steel, Nagoya, Japan) in the MEG Center of Ricoh Company, Ltd., in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…In healthy populations, the amplitude and latency of MMN/MMF is considered an indicator of change detection and has been used to probe speech discrimination 27 , 28 . In individuals with ASD, a number of studies have reported atypical MMN/MMF 29 35 and MMN/MMF is thought to be an indicator that physiologically explains core symptoms 31 , language impairment/delay 32 , 34 and preference for human voices 33 . Individuals with ASD showed a reduced MMF amplitude response in the left hemisphere compared to that of control subjects 34 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speech‐language processing atypicalities are common in autism. Impaired basic sensory‐perceptual processing of speech has been demonstrated in numerous EEG, MEG and fMRI studies (Lepisto et al ., ; Kujala et al ., ; Herringshaw et al ., ; Yoshimura et al ., ), suggesting that language atypicalities may be rooted in part in sensory processing deficits for speech stimuli. In this issue, Finch et al .…”
Section: Social Processing and Imitation In Asdmentioning
confidence: 99%